Correlation attacks on stream ciphers - Arslan Emirleroğlu, Zernişan (My University, 2001)
Dizi şifreleme algoritmalarında kullanılan kayar anahtar üreteçleri,çoğunlukla doğrusal geri beslemeli öteleyici tabanlı sistemlerdir. Bu tip sistemleri kırmak için gereken deneme miktarı, ilişkiye bağışıklık metodları ile azaltılabilir. Bu metodlara dayalı birçok saldırı yöntemi geliştirilmiştir. Bu tezde, kodlama teorisine dayanan yöntemlerden biri ayrıntıları ile incelenecektir. Bu yöntem daha önce geliştirilmiş olan metodların aksine, herhangi bir geri besleme polinomu kullanıldığında da etkili olmaktadır. Bir bilgisayar yazılımı ile bahsedilen yöntemin doğruluğu gösterilecek ve performans analizi verilecektir. Anahtar Sözcükler : Doğrusal geri beslemeli öteleyiciler, İlişkiye bağışıklık metodları, Viterbi kod çözme algoritması.

ABSTARCT Pseudorandom sequences based on Linear Feedback Shift Registers have been proposed for many cryptographic applications. In this correspondence, it is known that the number of trails to break these types of ciphers can be significantly reduced by using correlation methods. Several fast correlation attacks proposed based on this idea. In this thesis, we will give the details of one of the fast correlation attacks based on the theory of convolutional codes. This attack uses new methods which can be applied to arbitrary LFSR feedback polynomials, in opposite to the previous methods, which mainly focus on feedback polynomials of low weight. We will demostrate the validity of this method by a software implementation. Upon our computer program, the performance analysis of the method will also be given. Key Words: Linear Feedback Shift Registers, Correlation Attacks, Viterbi Decoding
Keywords: bilgisayar bilimi; Bilgisayar Mühendisliği; Çoklu işlem; Genel Konular; İşlem tarzları; Veri işleme